Immunomodulatory Activity of Chlorophytum borivilianum Sant. F - Thakur, Mayank (Oxford University Press, 2007)
Chlorophytum borivilianum Santapau & Fernandes (Liliaceae) is a very popular herb in traditional Indian medicine and constitute a group of herbs used as ‘Rasayan’ or adaptogen. Ethanolic extract of the roots and its sapogenin were evaluated for their immunomodulatory activity. Effect of azathioprine-induced myelosuppresion and administration of extracts on hematological and serological parameters was determined. Administration of extracts greatly improved survival against Candida albicans infection. An increase in delayed-type hypersensitivity response (DTH), % neutrophil adhesion and in vivo phagocytosis by carbon clearance method was observed after treatment with extracts. Immunostimulant activity of ethanolic extract was more pronounced as compared to sapogenins. The results, thus justifies the traditional use of C. borivilianum as a rasayana drug.